A new tool to measure training load in soccer training and match play - Rebelo, A.; Brito, J.; Seabra, A.; Oliveira, J.; Drust, B.; Krustrup, P. (International Journal of Sports Medicine, 2012)
An accurate evaluation of training load is paramount for the planning and periodization of training. The aim of the present study was to evaluate the relationship between a new method to monitor training load in soccer (Visual Analogic Scale training load; VAS-TL), and two established heart rate-based methods (TRIMP and Edwards' method). 51 soccer players (age 15.6±0.3 years) answered 2 questions to assess perceived exertion and fatigue (VAS1-TL, and VAS2-TL) after training sessions and official matches. Performance in the Yo-Yo tests, VAS scores and heart rate of training sessions and matches, and match activity were analysed. We found significant correlations (r=0.60-0.72; p<0.05) between VAS-TL, TRIMP, and the Edwards' training load method, with the highest correlations achieved in the matches. Although the different methods to monitor training load were correlated with the distance covered during the match (r=0.53-0.78; p<0.05), only VAS1-TL was associated with high-intensity activities (r=0.43-0.54; p<0.05). The new VAS-based perceived exertion method to monitor training load is easy to apply and is sensitive to differences in positional role and physical capacity. Thus, the applied method may be used in addition to the usual training load methods, allowing for daily quantification of individual training load in soccer.